Technical Foundations of GIS for the planning and management of the educational sector in the city of Nasiriyah - Dakhil, Ali fattah (Computer Engineering and Applications Journal, 2019)
The local government of the city of Nasiriyah has always appealed for a number of problems which it described as the difficult problems facing the reality of education in the city of Nasiriyah in Iraq, pointing to a large shortage of school buildings and educational staff and overcrowded classrooms. In order to improve the status of education in general and in the city of Nasiriyah in particular, the researcher presented in this paper a number of methods and modern techniques, which are considered as the basis of the context of the unit of GIS in the Directorate of Education Dhi-Qar to study the current reality of the educational institution and to identify the foci of these problems to control and solve them in an effective and rapid manner. In this research, the programming, analytical and statistical methods of the ArcGIS program and Python programming language were used. The researcher concluded that following these principles leads to locating the focal points of the problems of the educational sector in the city of Nasiriyah, located in the Eastern Ring and the southeast of the city. Several recommendations have been made in this research to solve these problems.